2017
DOI: 10.1042/bsr20160330
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale hybrid systems based on carbon nanotubes for biological sensing and control

Abstract: This paper provides a concise review on the recent development of nanoscale hybrid systems based on carbon nanotubes (CNTs) for biological sensing and control. CNT-based hybrid systems have been intensively studied for versatile applications of biological interfaces such as sensing, cell therapy and tissue regeneration. Recent advances in nanobiotechnology not only enable the fabrication of highly sensitive biosensors at nanoscale but also allow the applications in the controls of cell growth and differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…As both graphene and CNTs are composed exclusively of carbon, they exhibit high biocompatibility and easy functionalization and consequently are used for a wide range of devices, particularly, biosensors. 35,36…”
Section: One- and Two-dimensional Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…As both graphene and CNTs are composed exclusively of carbon, they exhibit high biocompatibility and easy functionalization and consequently are used for a wide range of devices, particularly, biosensors. 35,36…”
Section: One- and Two-dimensional Materialsmentioning
confidence: 99%
“…The diameter of an swCNT is typically 1-2 nm, while the diameter of an mwCNT ranges from 2 nm to over 100 nm. 35 The length of the nanotubes can reach up to ~0.5 m, although typically shorter (mm to cm) length tubes are produced. CNTs are commonly synthesized on a solid support using surface-programmed assembly methods and can have either metallic or semiconductor properties with various band gaps, depending on the bonding structure.…”
Section: One-and Two-dimensional Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescence-based techniques (total internal reflection fluorescence microscope, confocal microscopy and fluorescence correlation spectroscopy), opposed or combined to force-based techniques (optical trap, magnetic trap and atomic force microscope) (1)(2)(3)(4), offer the possibility to study molecules one at a time and to highlight reaction pathways and reaction intermediates that ensemble methods tend to hide because of their effect of averaging (5). More recently, another approach has been emerging based on single-molecule field-effect transistors (smFETs), in which an individual molecule is immobilized on a nanoscale electrical circuit, such as a carbon nanotube (6)(7)(8)(9)(10)(11)(12) or silicon nanowire (13)(14)(15)(16). By recording fluctuations in the electrical conductance of such circuits, studies have reported the realtime monitoring of transitions between different conformational states, such as hybridization (17)(18)(19)(20), folding events in nucleic acids (17,21), enzymatic catalysis with a ultra-high sensitivity and specificity (22,23), and also other applications in biology and medicine, such as imaging (24,25) and drug delivery (26,27) to cancer and brain.…”
Section: Introductionmentioning
confidence: 99%
“…The polymerization of MWNTs with PCA starts with the acid-functionalized MWNTs (fMWNT) and is followed by the addition of PCA, which covalently joins carboxylic functional groups of PCA and fMWNTs via a cleavable ester, obtaining polycitric acid-MWNTs (PMWNTs), an interesting material for nanomedicine applications [17,27,28,30,32]. Although in cell therapy, mesenchymal stem cells (MSCs) cultured on scaffolding are a real option in the field of tissue engineering [33] for generate or repair of new tissue [8,9,34,35], one of the major limitations is still the lack of anchoring between the damaged tissue and the cells that are supplied, because the MSCs applied by suspension directly in damaged areas produce little or null improvements on the surrounding damaged tissue [36] by transdifferentiation effect. Thus, the production of adequate scaffolds for proliferation and anchorage of MSCs is a fundamental aspect for future investigation [37] Despite that polymerized CNTs with other materials have effects on the MSC behavior, promoting adhesion [18,[38][39][40], changing stem cell's shape [7,8,41,42], and providing signals that may promote proliferation or differentiation [18], it is unknown if polymerized CNTs with PCA could help as intermediaries or structurally could act as a kind of staple between the extracellular matrix of a damaged tissue with the extracellular matrix of MSCs previously treated in vitro with PMWNT before injected.…”
Section: Introductionmentioning
confidence: 99%